Mucosal biomarkers of colorectal cancer risk do not increase at 6 months following sleeve gastrectomy, unlike gastric bypass. (15th October 2013) - Kant, Prashant; Perry, Sarah L.; Dexter, Simon P.; Race, Amanda D.; Loadman, Paul M.; Hull, Mark A.
Abstract : Objective: The hypothesis that sleeve gastrectomy (SG) is not associated with an increase in mucosal colorectal cancer (CRC) biomarkers, unlike Roux‐en‐Y gastric bypass (RYGB), was tested. Design and Methods: Rectal mucosa, blood, and urine were obtained from morbidly obese patients ( n = 23) before and after (median 28 months) SG, as well as from nonobese controls ( n = 20). Rectal epithelial cell mitosis and apoptosis, crypt size/fission, and pro‐inflammatory gene expression were measured, as well as systemic inflammatory biomarkers, including C‐reactive protein (CRP). Results: The mean pre‐operative body mass index in SG patients was 65.7 kg/m 2 (24.7 kg/m 2 in controls). Mean excess weight loss post‐SG was 38.2%. There was a significant increase in mitosis frequency, crypt size, and crypt fission (all P < 0.01) in SG patients versus controls, as well as evidence of a chronic inflammatory state (raised CRP and mononuclear cell p65 NFκB binding), but there was no significant change in these biomarkers after SG, except CRP reduction. Macrophage migration inhibitory factor mRNA levels were increased by 39% post‐SG ( P = 0.038). Conclusions: Mucosal biomarkers of CRC risk do not increase at 6 months following SG, unlike RYGB. Biomarkers of rectal crypt proliferation and systemic inflammation are increased in morbidly obese patients compared with controls.